Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Cerita Pada Materi Aturan Sinus dan Kosinus Kelas X Mipa 1 SMA N 1 Sipora Kabupaten Kepulauan Mentawai - Karmila Karmila; Audra Pramitha Muslim; Dewi Yuliana Fitri (Horizon, 2023)
ABSTRACTThe background of this research is in the difficulties experienced by students in solving maths in the form of story. The porpose of this study is to describe students’ difficulties in solving the Rules Sinus and Cosinus. The research method is a descriptive method with a quantitative approach. This subject of this research was a class X MIPA 1 SMAN 1 Sipora which was 24 students, 10 male and 14 female students. Sampling technique is purposive sampling. The instruments used to collect data are description test and interviews. The test result were analyzed based on the indicator of difficulty completing the story problems. The result of this study describe the number of students having difficulty completing the take of learning the Rules Sinus and Cosinus. 33% of students have difficulty translating taks and about 25% of students having difficulties making math models, 25% of students have difficulties in completing math models, 17% of students have difficulties in expressing a final answer. The largest difficulties that students experienced when working on stories lies in translating questions, completing math models, creating math models, and declaring the final answer.